The End of Akıncı Corps in The Ottoman Empire - Mustafa Alkan (Gazi Akademik Bakış)
It has been known that the Akıncıs were in the Ottoman Empire an extention of the corps which provided the border security of the Turkish states. They were named in the Seljuki period as “margraves”. Even the Ottomans were one of these margraves. Adopting a more centralist policy, the Ottoman Empire didn’t leave the border security to margraves as it was the case in Seljuks, but they assigned this job to some akıncı families. Evrenesoğulları in Albania and Dalmatia, Mihal-oğulları in Bosnia, Semendire and Serbia, Malkoç-oğulları in Silistre and Turhan-oğulları in Mora were the most famous ones among these families. The missions of the Akıncıs was to ensure the frontier security, to undertake reconnaissance mission in the regions which would be conquered, to gather intelligence, to raid the enemy territories and to act advanced guards, which was called as the fifth column activities at that time. It is assumed that Evranos Bey established the Akıncı corps. They were the light cavalry forces and had a certain organizational structure. Those with manor were registered in the account book with their descriptions. Their number exceeded fifty thousand during the period of Suleyman the Magnificient. The number of Akıncıs continued to increase until the 16th Century. In 1595, during the attacks carried out against Walachia Voivodina Mihail, who rebelled, the Akıncıs which stayed behind the Ottoman army, which was retreating over the wooden bridge, were nearly destroyed due to the inconsiderate act of Grand Vizier Sinan Pasha. After that incident the Akıncıs could not recover and their mission was undertaken by the Akkerman, Dobruca and Bucak Tatars and Crimea Khanate’s forces. With the exception of the short research of İ. Hakkı Uzunçarşılı, which is based on secondary sources, no serious study has been produced on the guild of Akıncıs by benefiting from the manorial books, muhimme books and local registry books. In this study the “Yergöğü bridge incident” which brought the end of the Akıncıs will be examined by referring to the secondary works of that time such as Mustafa Ali’s Künhül Ahbar and İbrahim Peçevi’s Tarih-i Peçevî. Registers of the Akıncıs in mühimme books of 1595 will also be taken into consideration. The findings will also be reflected in the conclusion.